Antioxidant Activities of Scrub Body Lotion Extract of Surian Leaves (Toona sinensis) with Powder Scrub Date Seeds (Phoenix dactylifera) - Uce Lestari; Yuliawati Yuliawati; Fathnur Sani; Yuliana Yuliana; Muhaimin Muhaimin (Indonesian Journal of Pharmaceutical Science and Technology, 2022)
Free radicals from exposure to ultraviolet radiation (UVB) cause dull, rough, dry, cracked skin andpremature aging so that they can damage skin tissue and result in fatal skin cancer. To prevent this,antioxidants are needed. Plants that have potential as antioxidants are Surian leaves and date seedswhich contain lots of flavonoids and phenolics. To make it easier to use, it is processed into a scrubbody lotion using a date seed powder scrub (Phoenix dactylifera). This study aimed to find a scrubbody lotion formula that has the best physical properties and is stable during storage and the bestformula has the strongest antioxidant activity. Each formula contains ethanol extract of Surian leaves(Toona sinensis) with a concentration of 0.1%; 0.3%; 0.5%; 0.7%; 0.9%. After that, an evaluationof the physical properties of scrub body lotion preparation was carried out. From the results of theevaluation of the physical properties of the best scrub body lotion preparations, stable in storage andhedonic tests and safe for irritation tests, formula 5 contains ethanol extract of surian leaves with aconcentration of 0.9% and has an antioxidant activity of IC50 28,554 ppm with a very strong category.